Incidencia del texto didáctico de computación del octavo año de educación básica del colegio de bachillerato Ismael Pérez Pazmiño, de la ciudad de Machala, durante el período lectivo 2012 - 2013 - Bahamonde Espinoza, Melanea (2015)
Currently in educational institutions cann´t progress without teaching resources, teaching with technology as a support tool, has become an indispensable resource for the proper teaching-learning process, therefore, we now live in a knowledge society where everyone should be at par with the technological changes that we find every day. Thus it becomes essential support for teachers in developing classroom activities, and achieve significant learning achievement of students, raising their academic level. The results of this study served as an argument to support this work, is based on research and observations to the problems experienced daily in this Education Unit, for the lack of easy text and interactive teaching management, which give a total change to the attention of the students, raising their level of concentration and real classrooms becoming facilitators of learning spaces, and taking students as active participants thereof, thereby causing the development of the declared contents of the curriculum and improving cognitive development of the student. This text is then essential educational support for teachers. Allowing improve student academic performance, teacher professionalization and institutional level campus.